Theileria parva candidate vaccine antigens recognized by immune bovine cytotoxic T lymphocytes - Graham, S.P.; Pelle, Roger; Honda, Y.; Mwangi, David Miano; Tonukari, N.J.; Yamage, M.; Glew, E.J.; Villiers, Etienne P. de (National Academy of Sciences, 2006)
East Coast fever, caused by the tick-borne intracellular apicomplexan parasite Theileria parva, is a highly fatal lymphoproliferative disease of cattle. The pathogenic schizont-induced lymphocyte transformation is a unique cancer-like condition that is reversible with parasite removal. Schizont-infected cell-directed CD8+ cytotoxic T lymphocytes (CTL) constitute the dominant protective bovine immune response after a single exposure to infection. However, the schizont antigens targeted by T. parva-specific CTL are undefined. Here we show the identification of five candidate vaccine antigens that are the targets of MHC class I-restricted CD8+ CTL from immune cattle. CD8+ T cell responses to these antigens were boosted in T. parva-immune cattle resolving a challenge infection and, when used to immunize naïve cattle, induced CTL responses that significantly correlated with survival from a lethal parasite challenge. These data provide a basis for developing a CTL-targeted anti-East Coast fever subunit vaccine. In addition, orthologs of these antigens may be vaccine targets for other apicomplexan parasites.